Bimbingan Teknis Peliputan Berita Dan Pengelolaan Website - Irawadi, Syafrul; Saftari, Maya; Iswanto, Yuni; Rosydian M, Ahmad; Sariman, Sariman (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
Bawaslu of the Bangka Belitung Islands Province as the election supervisory body in the province of Bangka Belitung also considers it important to provide information and manage the website properly. For this reason, Bawaslu cooperates with universities and the government to provide technical guidance and training for news and website managers to improve the ability of managers. This technical assitence involves resource persons who are experts in their fields from various agencies. STMIK Atma Luhur as a university accommodates training activities by involving the community service team. The PKM team consists of 3 lecturers and 2 students. The activity took place on December 7, 2019 which took place at the Grand Vella Hotel Bangka. The training participants came from 7 districts/cities with every cities has to send 3 participants. This activities started from morning to evening. The method in this PKM activity is training and technical guidance with the lecture method from the speakers. The activities in addition to the material provided, practical activities were also held to demonstrate how to properly manage the website and news coverage techniques to provide good and correct information. The results of the evaluation of this activities carried out, it was found that the participants gained knowledge and knowledge that could improve their ability to manage the Bawaslu news and website